Lima Barreto e João Antônio: traces of a marginal literature - Pantano, Andreia Aparecida [UNESP]; Marques, Francisco Claudio Alves [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2024)
In this text we seek to establish some connections between the writers Lima Barreto and Jo & atilde;o Ant & ocirc;nio, based on Jo & atilde;o Ant & ocirc;nio's short story Frio, published in 1963 in his book Malagueta, Perus e Bacana & ccedil;o, , and Lima Barreto's short stories O Moleque (1920) and O filho de Gabriela (1915). These texts made us think about the situation of exclusion and marginality of the so-called invisible, as presented by these writers, so that, through their eyes, we can see in contemporary times situations that, despite being temporally distant, seem very close to us. In view of this, the methodology used involved the careful reading of the short stories as well as the specific theoretical framework on the topic.
Keywords: Lima Barreto; Jo & atilde;o Ant & ocirc;nio; Marginal literature